KERAGAMAN JAMUR PADA LOG DAN KAYU GERGAJIAN NYATOH (Palaquium sp) (PERENNIAL, 2019)
Wood is one medium that can be a place to grow fungus. The chemical components forming wood in the form of holocellulose and lignin which can be overhauled by fungi into simple compounds are a food source for the fungus. This study aims to identify the type of fungus that grows on the log and or sawn wood of Palaquium sp so that it can provide information about the diversity of fungal species, both useful and those that are pathogenic. The process of identifying mushrooms is done by observing the macroscopic and microscopic characteristics of the fungus. The macroscopic characteristics observed were mushroom color and mushroom fruit body shape. Observations of microscopic features include hyphae, spores, sporangium, conidia, and conidiophores. Macroscopic and microscopic observations identified eight types of fungi that grow on real wood, namely Dacryopinax spathularia, Pycnoporus sanguineus, Schizophyllum commune, Cunninghamella echinulata, Penicillium, Trichoderma, Absidia ramosa and Aspergillus. There are six types of fungi which are wood rot fungi, namely D. spathularia; P. sanguineus; S. commune; Penicillium, Trichoderma, and Aspergillus. The other two types are coloring fungi, namely C. echinulata and A. ramosa.
Keywords: Diversity; fungi; Palaquium sp